Interactive learning in economic education: integrating LearningApps.org tasks into Moodle - Roman M. Horbatiuk; Uliana T. Dudka; Vitalii V. Kabak; Liliia Z. Rebukha (Academy of Cognitive and Natural Sciences, 2024)
This paper explores the use of interactive learning tools in economic education. Specifically, it examines how the LearningApps.org platform can be integrated into the Moodle learning management system to create engaging and effective learning activities for economic courses. The paper outlines the benefits of interactive learning, reviews relevant literature on using technology in economic education, and provides examples of interactive LearningApps.org exercises for topics in economics. The results indicate increased student motivation and improved learning outcomes when using LearningApps.org in Moodle. The paper concludes that combining interactive tools like LearningApps.org with a system like Moodle can enhance economic instruction and recommends further research into instructional design strategies for integrating educational technologies.